CYP1A2 and tobacco interaction: a major pharmacokinetic challenge during smoking cessation. (2nd January 2021) - Barrangou-Poueys-Darlas, Malcolm; Guerlais, Marylène; Laforgue, Edouard-Jules; Bellouard, Ronan; Istvan, Marion; Chauvin, Pascale; Guillet, Jean-Yves; Jolliet, Pascale; Gregoire, Matthieu; Victorri-Vigneau, Caroline
Abstract: Smoking cessation is underestimated in terms of drug interactions. Abrupt smoking cessation is common in cases of emergency hospitalization and restrictions of movement. Tobacco is a known cytochrome P450 1A2 (CYP1A2) inducer, its consumption and withdrawal can lead to major pharmacokinetic drug interactions. Nevertheless, references do exist, but may have different results between them. The objective of our work was to establish the broadest and most consensual list as possible of CYP1A2 substrates treatments and propose a pharmacological approach. We searched the widest possible list of CYP1A2 substrates based on various international references. We compared the references and defined probability and reliability scores of our results to sort the substances based on the scores. For the 245 substances identified as CYP1A2 substrates, we focused on the 63 CYP1A2 substrates with both probability and reliability scores >50%. Our work establishes adaptive pharmacological approaches for the management of patients initiating smoking cessation which must be integrated into the management of smoking cessation. Pharmacologists can now adopt adaptive pharmacological approaches to complement patient-specific clinical information about smoking cessation by considering pharmacokinetic risk. This work establishes an unprecedented list. It should guide in the care of patients initiating smoking cessation to prevent pharmacokinetic drug interactions.